Negotiating with Colonial Modernity: The New Minangkabau Elite in Bukittinggi City Early 20th Century - Andoni, Yudhi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2024)
The emergence of a new elite in Minangkabau, flourishing in the modern milieu of Bukittinggi city at the beginning of the 20th century, represents a pivotal case study in the dynamics of colonial modernity. These individuals distinguished themselves in the economic and intellectual domains, as well as in the authentication of symbolic status through lifestyle emulation of the Dutch. However, their integration into the social circles of both traditional and modern communities in Bukittinggi was met with limited acceptance. This phenomenon underscores a society that embraced novel perspectives on the colonial world without succumbing to colonialist ideologies. This raises pertinent inquiries: who were these new elites? Why did they seek recognition within their modern context in Bukittinggi despite existing within a reality of modernity? And what was the nature of the inclusivity process for these new elites as modernists, without becoming colonialists? This discourse elucidates the process by which the new Minangkabau elite negotiated colonial modernity in Bukittinggi between 1905 and 1942. The findings reveal that the successful negotiation of colonial modernity by the new Minangkabau elite served as a mode of restraint as well as alienation from the social realities of Bukittinggi. Firstly, the negotiation facilitated broader participatory avenues for the new elite of Minangkabau in early 20th-century Bukittinggi. Secondly, it paved the way for them to independently craft mediums of intellectual and inclusive modernity. Thirdly, this negotiation led to the creation of new cultural forms that amalgamated three essential values of early 20th century Bukittinggi: tradition, colonialism, and Islam.